The in vitro digestion fates of diacylglycerol under different intestinal conditions: a potential lipid source for lipid indigestion patients - Qingqing Xu; Weifei Wang; Dongxiao Sun-Waterhouse; Qian Zou; Menglei Yan; Xuan Liu; Dongming Lan; Yonghua Wang (Food Science and Human Wellness)
The in vitro digestion models mimicking the gastrointestinal (GI) tract of general population and lipid indigestion patients (with lower levels of bile salts or pancreatic lipase) were selected to investigate whether diacylglycerols (DAGs) are potential good lipid sources for these patients. Linseed oil-based DAG (LD) and linseed oil (LT) were selected. LD-based emulsion ((83.74 ± 1.23)%) had higher lipolysis degree than LT-based emulsion ((74.47 ± 1.16)%) when monitoring the GI tract of normal population as previously reported. Indigestion conditions seriously decreased the digestive degree of LT-based emulsion ((40.23 ± 2.48)%–(66.50 ± 3.70)%) while showed less influence on LD-based emulsion ((64.18 ± 2.41)%–(81.85 ± 3.45)%). As opposed to LT-based emulsion, LD-based emulsion exhibited preference for releasing unsaturated fatty acids (especially oleic acid and α-linolenic acid) due to their different glycerolipid compositions. LD-based emulsion showed potential for providing lipids and nutrients (including essential fatty acids) for lipid indigestion patients.